2018
DOI: 10.1017/s1041610218000236
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation and design of a short depression screening tool in Turkish older adults

Abstract: GDS-15 is the most powerful screening scale for geriatric depression. GDS-4 and GDS-5 are not eligible for depression screening in Turkish older adults. All new short scales are valid and reliable, and TGDS-4 is a practical, less time-consuming option for daily practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 39 publications
1
24
0
1
Order By: Relevance
“…Evaluation of oral functions might be one of the strengths of KCL. In the present study, another question with limited power to assess frailty according the kappa value was the 24th question that queried about “feeling helpless.” In previous studies of Turkish older adults, the questions about “feeling helpless” have been shown to have low discriminative power in screening for depression . These reasons might explain the low sensitivity and specificity of the frail candidates of the KCL and the control group.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Evaluation of oral functions might be one of the strengths of KCL. In the present study, another question with limited power to assess frailty according the kappa value was the 24th question that queried about “feeling helpless.” In previous studies of Turkish older adults, the questions about “feeling helpless” have been shown to have low discriminative power in screening for depression . These reasons might explain the low sensitivity and specificity of the frail candidates of the KCL and the control group.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies of Turkish older adults, the questions about "feeling helpless" have been shown to have low discriminative power in screening for depression. 16 These reasons might explain the low sensitivity and specificity of the frail candidates of the KCL and the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic characteristics (age, gender, educational status, and marital status) and detailed geriatric evaluation were recorded. In detailed geriatric evaluation, The Clinical Dementia Rating scale (CDR) (Morris, 1993), The Montreal Cognitive Assessment scale (MOCA) (individuals who were educated for nine years or more) (Nasreddine et al, 2005), the Mini-Mental State Examination (MMSE) (individuals who were educated for five to eight years) (Folstein et al, 1975), Cognitive Status Test (COST) (individuals who were educated four years or less, or illiterate) (Babacan-Yildiz et al, 2013) and the Clock Drawing Test (Shulman, 2000) were used for neurocognitive assessment; The Yesavage Geriatric Depression Scale (YGDS) (Durmaz et al, 2018;Dokuzlar et al, 2018) for emotional state assessment; and The Lawton-Brody Instrumental Daily Living Activity Scale (IADL) (Lawton and Brody, 1969) and Barthel index (BI) (Mahoney and Barthel, 1965) for daily living activities.…”
Section: Methodsmentioning
confidence: 99%
“…Elderly people who experience depression are less likely to show affective symptoms than younger generations. One of the most commonly used screening instruments to measure depression status in older adults and has proven efficacy includes the Geriatric Depression Scale (GDS)-15 (22). Older adults who experience depression has a tendency to experience a decrease in the quality of life both bio-psycho-social-spiritual.…”
Section: Discussionmentioning
confidence: 99%